2022
DOI: 10.1186/s12904-022-01041-z
|View full text |Cite
|
Sign up to set email alerts
|

“I want to live, but …” the desire to live and its physical, psychological, spiritual, and social factors among advanced cancer patients: evidence from the APPROACH study in India

Abstract: Background The limited access to palliative care resources along with the social stigma around cancer largely explains the poor quality of life (QoL) of Indian advanced cancer patients. As advanced cancer patients with poor QoL often harbour a desire for hastened death (DHD), it is imperative to understand factors affecting DHD, or the desire to live (DTL) among advanced cancer patients in India. We aim to examine the relationship between DTL and physical, psychological, spiritual, and social f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…It is common among adults of any age to struggle to live within the dichotomy of double awareness ( Umaretiya et al, 2023 ; Avery et al, 2020a ). However, the inconsistent cues our participants perceived receiving from healthcare providers may be more common among the YA population ( Joad et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is common among adults of any age to struggle to live within the dichotomy of double awareness ( Umaretiya et al, 2023 ; Avery et al, 2020a ). However, the inconsistent cues our participants perceived receiving from healthcare providers may be more common among the YA population ( Joad et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…They work in a resource-poor environment and at times feel helpless to deal with the complex socio-economic and medical problems the clients come across. 17 Meta-analytical estimations by Gómez-Urquiza et al reported a high level of burnout (24-30%) among palliative care providers with high in uence on depersonalization, emotional exhaustion, and low personal accomplishment and suggests an improvement in the working environment. 18 Compared to the palliative care providers of an institution, community health care workers suffer more con icts because of their limited training, workload and lack of access to resources.…”
Section: Discussionmentioning
confidence: 99%